The performance of community health workers in the management of multiple childhood infectious diseases in Lira, northern Uganda - a mixed methods cross-sectional study - Phillip Wanduru; Moses Tetui; Doreen Tuhebwe; Michael Ediau; Monica Okuga; Christine Nalwadda; Elizabeth Ekirapa-Kiracho; Peter Waiswa; Elizeus Rutebemberwa (Taylor & Francis Group, 2016)
Background: Community health workers (CHWs) have the potential to reduce child mortality by improving access to care, especially in remote areas. Uganda has one of the highest child mortality rates globally. Moreover, rural areas bear the highest proportion of this burden. The optimal performance of CHWs is critical. In this study, we assess the performance of CHWs in managing malaria, pneumonia, and diarrhea in the rural district of Lira, in northern Uganda. Designs: A cross-sectional mixed methods study was undertaken to investigate the performance of 393 eligible CHWs in the Lira district of Uganda. Case scenarios were conducted with a medical officer observing CHWs in their management of children suspected of having malaria, pneumonia, or diarrhea. Performance data were collected using a pretested questionnaire with a checklist used by the medical officer to score the CHWs. The primary outcome, CHW performance, is defined as the ability to diagnose and treat malaria, diarrhea, and pneumonia appropriately. Participants were described using a three group performance score (good vs. moderate vs. poor). A binary measure of performance (good vs. poor) was used in multivariable logistic regression to show an association between good performance and a range of independent variables. The qualitative component comprised seven key informant interviews with experts who had informed knowledge with regard to the functionality of CHWs in Lira district. Results: Overall, 347 CHWs (88.3%) had poor scores in managing malaria, diarrhea, and pneumonia, 26 (6.6%) had moderate scores, and 20 (5.1%) had good scores. The factors that were positively associated with performance were secondary-level education (adjusted odds ratio [AOR] 2.72; 95% confidence interval [CI] 1.50-4.92) and meeting with supervisors in the previous month (AOR 2.52; 95% CI 1.12-5.70). Those factors negatively associated with CHW performance included: serving 100-200 households (AOR 0.24; 95% CI 0.12-0.50), serving more than 200 households (AOR 0.22; 95% CI 0.10-0.48), and an initial training duration lasting 2-3 days (AOR 0.13; 95% CI 0.04-0.41). The qualitative findings reinforced the quantitative results by indicating that refresher training, workload, and in-kind incentives were important determinants of performance. Conclusions: The performance of CHWs in Lira was inadequate. There is a need to consider pre-qualification testing before CHWs are appointed. Providing ongoing support and supervision, and ensuring that CHWs have at least secondary education can be helpful in improving their performance. Health system managers also need to ensure that the CHWs' workload is moderated as work overload will reduce performance. Finally, although short training programs are beneficial to some degree, they are not sufficient and should be followed up with regular refresher training.